2021
DOI: 10.1177/1038416221994208
|View full text |Cite
|
Sign up to set email alerts
|

Schematic analysis of job application letters by Malaysian graduates

Abstract: This study applied a “moves analysis” approach to examine job application letters written by 25 Malaysian graduates obtained from an outsourcing organisation in Kuala Lumpur, Malaysia. The letters were analysed as to whether they adhered to the seven aspects of the “moves structure” used to analyse job applications (i.e. establishing credentials, introducing candidate, detailing advantages, enclosing relevant documents, ending appropriately, offering incentives, and using pressure tactics). Additionally, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A review of the existing literature on ESP analysis of professional discourse has shown that GA has been used in many areas such as academic writings (e.g., Alharbi, 2021;Edusei, 2015;Musa, 2014;Lakic, 1997), business emails (e.g., Mehrpour & Mehrzad, 2013;Giménez Moreno, 2010), business letters (e.g., Kyei & Afful, 2021;Jalilifar & Beitsayyah, 2011;Santos, 2002), job application letters (De Mello et al, 2021;Thumnong, 2017;Henry & Roseberry, 2001), and news presentation (e.g., Agbaglo et al, 2021;Amoakohene, 2017). However, studies on analyzing the minutes of meeting as a genre in similar contexts and similar professional settings have been scarce.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the existing literature on ESP analysis of professional discourse has shown that GA has been used in many areas such as academic writings (e.g., Alharbi, 2021;Edusei, 2015;Musa, 2014;Lakic, 1997), business emails (e.g., Mehrpour & Mehrzad, 2013;Giménez Moreno, 2010), business letters (e.g., Kyei & Afful, 2021;Jalilifar & Beitsayyah, 2011;Santos, 2002), job application letters (De Mello et al, 2021;Thumnong, 2017;Henry & Roseberry, 2001), and news presentation (e.g., Agbaglo et al, 2021;Amoakohene, 2017). However, studies on analyzing the minutes of meeting as a genre in similar contexts and similar professional settings have been scarce.…”
Section: Introductionmentioning
confidence: 99%